Moving from Virtual Reality Exposure-Based Therapy to Augmented Reality Exposure-Based Therapy: A Review - Baus, Oliver; Bouchard, Stéphane (Frontiers in Human Neuroscience, 2014)
This paper reviews the move from virtual reality exposure-based therapy (VRET) to augmented reality exposure-based therapy (ARET). Unlike virtual reality (VR), which entails a complete virtual environment (VE), augmented reality (AR) limits itself to producing certain virtual elements to then merge them into the view of the physical world. Although the general public may only have become aware of AR in the last few years, AR type applications have been around since beginning of the 20th century. Since, then, technological developments have enabled an ever increasing level of seamless integration of virtual and physical elements into one view. Like VR, AR allows the exposure to stimuli which, due to various reasons, may not be suitable for real-life scenarios. As such, AR has proven itself to be a medium through which individuals suffering from specific phobia can be exposed “safely” to the object(s) of their fear, without the costs associated with programming complete virtual environments. Thus, ARET can offer an efficacious alternative to some less advantageous exposure-based therapies. Above and beyond presenting what has been accomplished in ARET, this paper also raises some ARET related issues, and proposes potential avenues to be followed. These include the definition of an AR related term, the type of measures to be used to qualify the user’s experience in an augmented reality environment (ARE), the development of alternative geospatial referencing systems, as well as the potential use of ARET to treat social phobia. Overall, it may be said that the use of ARET, although promising, is still in its infancy but that, given a continued cooperation between clinical and technical teams, ARET has the potential of going well beyond the treatment of small animal phobia.